Perancangan dan Implementasi Arsitektur Sistem Informasi Complaint and Feedback Berbasis Web untuk Optimasi Layanan Publik Desa (Studi Kasus Desa Bitung Sari) - Muhammad Ikhsanudin; Endah Murtiana Sari; Silviana Windasari (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2026)
Public service is a core right of every citizen that should be fulfilled by the government, including at the community level (village). However, the management of local community complaints in Bitung Sari Village, In Bogor Regency, the system remains manual, which causes delays in addressing complaints, suboptimal efficiency, and suboptimal documentation of public grievances. This paper seeks to develop and implement a web-based complaint and feedback system to enhance the quality of public services at the village level. The present study employs the Waterfall approach, which consists of requirement analysis, system planning using Unified Modeling Language (UML), implementation through the Laravel framework and Filament platform, as well as functional evaluation using the Black Box testing technique. Data for this study were gathered through literature studies, interviews with village authorities, and discussions with local residents, and observations of the service process prior to system implementation. The results of this study demonstrate that the system enhances the submission of complaints, accelerates the follow-up process, and enhances the transparency and accountability of public services. Therefore, this system can serve as a digital solution for village public service delivery and has the capability to be implemented in other areas facing similar conditions issues.